Gambaran Tingkat Kecemasan pada Pasien Pre Operasi Laparascopy Cholesistectomy di Rumah Sakit Semarang - Umi Nuraini Umi Nuraini; Dwi Heppy Rochmawati; Wigyo Susanto (NAJ Nursing Applied Journal, 2025)
Preoperative anxiety in patients undergoing laparoscopic cholecystectomy is an important issue because it can affect the psychological and physiological condition, as well as the postoperative recovery process. This study aims to describe the level of anxiety in preoperative laparoscopic cholecystectomy patients at Sultan Agung Islamic Hospital (RSI) Semarang. This research used a quantitative descriptive design with a population of all preoperative laparoscopic cholecystectomy patients and a total sample of 91 respondents, selected using purposive sampling technique. Data collection was performed using a questionnaire, which was then analyzed univariately to obtain the frequency distribution of anxiety levels. The results showed that most respondents were in the elderly group (41.8%), male (79.1%), employed (75.8%), and had no medical history (72.5%). The majority of respondents experienced moderate anxiety (73.6%), followed by mild anxiety (23.1%) and severe anxiety (3.3%). These findings indicate that most patients experience moderate anxiety before the surgical procedure. These results can serve as a basis for healthcare providers to deliver psychological interventions to reduce preoperative anxiety, such as providing adequate information, emotional support, and relaxation techniques to improve patient comfort and readiness for the medical procedure.